Synchronization of breathing and aiming skills as a basis for training rifle shooters at a moving target - Ilyakhina, O.Yu.; Kadutskaya, L.A.; Domracheva, E.Yu. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop a pedagogical model for training rifle shooters at a moving target based on the synchronization of breathing and aiming skills. Methods and structure of the study. Conducted: analysis of scientific and methodological literature on the problem under study; analysis of training programs for rifle shooters at a moving target; generalization of advanced pedagogical experience in the field of training athletes. The study examined the components of a pedagogical model for training shooters; carried out: the choice of means and methods of training; implementation of the training program; ensuring control over the growth of sportsmanship and results in shooting among athletes. Results and conclusions. It was revealed that the motor action in shooting from a rifle at a moving target can be carried out in accordance with the target task only on the basis of coordination of muscle efforts in the production of a well-aimed shot. This is the basis for synchronizing breathing and aiming skills in the preparation of running target rifle shooters for competition. Based on this, motor memory arises, which stores a huge number of the simplest coordinations necessary for producing a well-aimed shot. The revealed components of the developed model most capaciously characterize the peculiarities of the training of shooters from a rifle at a moving target. The leading criterion for the effectiveness of the shooter training model is the synchronization of breathing and aiming skills. The use of the training model is aimed at ensuring a high level of development of the necessary muscles in rifle shooters at a moving target, increasing the level of sportsmanship, creating conditions for faster adaptation of athletes to the specific conditions of competitive activity.